Development of a Subjective Workload Assessment Technique Model as an Effort to Improve Performance Nurse in Home Inpatient Room Royal Prima Hospital - Ali Napiah Nasution; Muliate Tarigan; Ermi Girsang (Postgraduate, University of Mataram, 2023)
It is hoped that the performance of all medical and non-medical personnel at the Hospital will be in top condition. Nurses are expected to provide good service. This research aims to develop a subjective workload assessment technique model as an effort to improve the performance of nurses in the Inpatient Room at Royal Prima Hospital. This research is a quantitative study with a cross sectional study design which was carried out in the inpatient ward of the Royal Prima Hospital from June to July 2023. The population was 120 people. Respondents who were selected (inclusion) or excluded through the selection process were those who had more than 3 months of experience working in a care unit or related work. Data were analyzed univariate, bivariate and multivariate. The results of the research show that there is an influence of time pressure, working hour schedules, multiple roles, revetitive action on improving the performance of inpatient nursing personnel which is subjectively reasoned by inpatient nurses at Royal Prima Hospital. The variable that has the most dominant influence is the dual role variable.The suggestion of this research is that the health service should provide input in the context of continuous guidance to hospitals, especially in managing hospital management to improve better performance.